Leveraging financial markets for development how KfW revolutionized development finance - Volberding, Peter (Executive politics and governance, 2021)
"This is an excellent book on an increasingly important topic, and proves a valuable resource for academics, students, and policy-makers." -Stephany Griffith-Jones, Professor, Columbia University, USA "Peter Volberding addresses a long-standing issue of delivering effective financing for sustainable economic development. He does not simply provide the origin, evolution and challenges of marketized development financial instruments, he goes beyond!" -Désiré Kanga, Centre for Global Finance, SOAS University of London, UK "Peter Volberding's engaging account documents the actors and institutions-notably, the German state-owned KfW-that made this revolutionary change possible." -Beth Simmons, Professor, University of Pennsylvania, USA This book investigates how development institutions created and promoted marketized development financial instruments to increase the speed and scope of assistance by leveraging private financial markets for development objectives. To attract private investors, donor governments agreed to bear the risk in these new instruments in order to mobilize investment during times of political crisis. In particular, this book contends that Germany's KfW played an outsized role in the development of these new financial instruments, particularly in microfinance banks and structured funds, as KfW's unique institutional attributes and strong political support from the German government at critical junctures fostered financial innovation. Using over 70 interviews and a cache of newly released archival materials, this book documents how KfW and other development institutions created and promoted these marketized development financial instruments, and how they have become a pillar of modern development policy. Peter Volberding received his PhD from the Government Department at Harvard University, USA.